VD_FINDINFO Jug / 2024 / 132 vom 9. November 2023 - VD Tribunal cantonal (2023)
CONSTATATION DES FAITS, IN DUBIO PRO REO, FIXATION DE LA PEINE, CONCOURS D'INFRACTIONS | 47 al. 1 CP, 49 al. 1 CP, 10 al. 2 CPP (CH)